The influence of ethnicity on social media influencer towards customer purchase intention - Lim, Yi Thing (2021)
Social media in nowadays has become a daily basis, and there is not a single day when they do not habitually check their social media. Therefore, it is not surprising that social media platforms have become a significant marketing channel for nowadays. The past studies show there is a relationship between social media influencer and customers purchase intention. Nowadays a lot of organizations are searching for social media influencer as a marketing communication channel to attracted audience and consumers to buy their product and services. The latest data from Twitter and Annalect show that nearly 40% of Twitter users have purchased goods due to tweets from. However, there are still many organizations unable to utilize social media influencer as a proper communication channel. Organization selected the social media influencer based on their number of followers instead of the type of content they create. A lot of people believed that greater number of followers will bring greater number of purchasing (Tanner & Raymond, 2012). There is limited research which tells how ethnicity will involve in the study of social media influencer (Olaojo, 2020). Unlike others Western countries, Malaysia have multi ethnicities of citizens and each of the groups have their own cultural perspective towards any situation. This research is essential to provide insight and understand on how social media influencers in Malaysia will determine the content of social media marketing communications and will help improve the effectiveness of strategic communication and online business growth.